Non-zinc-rich water-based primer, preparation method and application
Through the non-zinc-rich water-based primer formula, the molecular structure of carboxyl, ester and metal complexing groups and polymer resins at multiple crosslinking sites are solved in the stability and weatherability of water-based primers. , realizes efficient anti-corrosion protection in harsh environments.
Patent Information
- Application Number
- CN202411619216.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing water-based primers have defects in stability and weather resistance, especially because the presence of phosphoric acid causes the emulsion-like primer to be unstable, and the traditional anti-rust agent has limited anti-corrosion effect in high humidity, high temperature and high salt spray environments.
Non-zinc-rich water-based primer formula, including main agent and curing agent, the main agent consists of water, dispersants, fillers, anti-rust agent, defoaming agent, aqueous organic bentonite, etc. The curing agent is composed of water-based curing agent and conditioning agent. The polymer resin through the introduction of molecular structures of carboxyl groups, ester groups and metal complexing groups is formed to form a stable complexing film, improve the antioxidant performance and self-healing ability of the coating, and pass through polymer resins with multiple crosslinking sites. Form a mesh structure to enhance the weather resistance of the coating.
It significantly improves the anti-rust effect of the coating on metal substrates, maintains long-term anti-corrosion protection in harsh environments such as high humidity, high temperature, high salt spray, etc., improves the weather resistance and stability of the coating, and avoids the phosphoric acid-induced Stability issues.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based primers, and more specifically, relates to a non-zinc-rich water-based primer, a preparation method and an application thereof. Background Art
[0002] Water-based paint has the advantages of low volatile organic compound (VOC) emissions, non-toxicity, and easy cleaning, which conforms to the current trend of environmental protection and health needs. However, despite the certain advantages of water-based paint in environmental protection, the existing technology still faces a series of challenges, especially in terms of paint stability and weather resistance. For example, some primers are based on water-based acrylic modified alkyd resins, and there are polyether segments on the resin molecular chain, and the water resistance of the paint film is not ideal. Some water-based primers are highly acidic due to the presence of phosphoric acid, making most emulsion primers unstable. Summary of the invention
[0003] 1. Technical issues to be resolved The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide a non-zinc-rich water-based primer, a preparation method and an application.
[0004] (II) Technical solution In order to achieve the above-mentioned object and other related objects, the present invention provides the following technical solutions: In the first aspect, a non-zinc-rich water-based primer is provided, including a main agent and a curing agent, wherein the main agent includes component A1 and component A2; the curing agent includes component B; component A1 includes the following raw materials: water, dispersant, filler, rust inhibitor, defoamer, filler wetting agent, and water-based organic bentonite; component A2 includes the following raw materials: water-based epoxy emulsion, defoamer, substrate wetting agent, water-based thickener, cosolvent, and anti-flash rust agent; component B includes the following raw materials: water-based curing agent, water, and regulator.
[0005] Preferably, the filler includes at least one of titanium dioxide, red iron oxide, yellow iron oxide, precipitated barium sulfate, talcum powder, wollastonite powder, and mica powder; and the rust inhibitor includes aluminum tripolyphosphate.
[0006] Preferably, the defoaming agent includes at least one of a silicone-based defoaming agent and a biopolysaccharide-based defoaming agent; the filler wetting agent includes an acrylate copolymer; the substrate wetting agent includes a polyoxyethylene ether; the aqueous thickener includes a cellulose thickener; the cosolvent includes at least one of propylene glycol monobutyl ether and dipropylene glycol monobutyl ether; the anti-flash rust agent includes at least one of sodium nitrite and a homemade anti-flash rust agent; and the regulator includes at least one of a homemade regulator and 2-amino-2-methyl-1-propanol.
[0007] Preferably, the preparation method of the silicone-based defoamer comprises the following steps: reacting amino-terminated polydimethylsiloxane with epoxidized vegetable oil to generate a copolymer; adding polyethylene glycol methacrylate, the copolymer, and dopamine hydrochloride to water, reacting under alkaline conditions, adding an initiator after the reaction is completed, and heating to polymerize, and after the reaction, cooling and stirring to room temperature to obtain the silicone-based defoamer.
[0008] Preferably, the method for preparing the biopolysaccharide-based defoamer comprises the following steps: dissolving the bioactive polysaccharide, adding vegetable oil and an emulsifier, and emulsifying under stirring to obtain the biopolysaccharide-based defoamer.
[0009] Furthermore, the bioactive polysaccharide includes at least one of gum arabic, xanthan gum and pectin.
[0010] Furthermore, the vegetable oil includes at least one of soybean oil, corn oil and olive oil.
[0011] Preferably, the preparation method of the homemade anti-flash rust agent comprises the following steps: preparing phytic acid into a phytic acid solution, adding polyquaternary ammonium salt and silica aerogel to the phytic acid solution to obtain a mixed solution; adding indium methanesulfonate and trifluoroacetic acid to the mixed solution, and after the reaction is completed, adding glycerol and water to obtain the homemade anti-flash rust agent.
[0012] Preferably, the preparation method of the homemade regulator comprises the following steps: preparing polymerized dopamine-modified graphene: preparing graphene oxide into a dispersion, then adding dopamine hydrochloride to the dispersion, reacting, then adding titanium dioxide nanoparticles, perfluorooctyltriethoxysilane, and ethanol, and after the reaction, centrifuging the reaction mixture, washing and drying to obtain polymerized dopamine-modified graphene; adding terminal hydroxyl polydimethylsiloxane and dimethylformamide in a container, stirring evenly, adding epoxy silane, reacting, and then adding polyethylene glycol and dibutyltin dilaurate, and after the reaction, adding an organosilicon compound to the reaction solution, and after the reaction is completed, concentrating, washing and drying to obtain an organosilicon polyether block copolymer; after the polyetheramine is dissolved, adding polymerized dopamine-modified graphene, organosilicon polyether block copolymer, triethanolamine, initiator, and ethylene glycol monoethyl ether, and after the reaction is completed, cooling to room temperature, adjusting the total volume, and obtaining a homemade regulator.
[0013] Preferably, the preparation method of the water-based curing agent comprises the following steps: reacting a polyamide resin and a polyether polyol to obtain a prepolymer, then cooling and adding a diisocyanate, adding triethoxysilane after the reaction, cooling and adding trimethylolpropane trimethacrylate after the reaction to obtain a mixed solution, dissolving an emulsifier and adding it to the mixed solution, stirring and cooling, and obtaining a water-based curing agent.
[0014] In a second aspect, a method for preparing the aforementioned non-zinc-rich water-based primer is provided, comprising the following steps: Ingredients: Mix the raw materials of component A1 evenly to obtain formula A1; Grinding: Grind the raw materials of component A2 and mix well to obtain formula A2; Blending: Mix formula A2 and formula A1 to obtain a coating; Mixing: Mix the raw materials of component B to obtain formula B, and mix the coating and formula B to obtain a non-zinc-rich water-based primer.
[0015] It should be noted that the final step of mixing is usually prepared on-site when it is needed.
[0016] In a third aspect, a composite material is provided, including a substrate, on which a non-zinc-rich water-based primer is formed into a dry film, and the thickness of the dry film is controlled to be 20-40 μm, wherein the non-zinc-rich water-based primer is prepared according to the preparation method of the non-zinc-rich water-based primer.
[0017] Preferably, the material of the substrate comprises steel.
[0018] 3. Beneficial technical effects Advantages of the present invention: The present invention improves the formula of non-zinc-rich water-based primers, so that the anti-rust effect of the coating on the metal substrate is greatly improved, and it can maintain long-term anti-corrosion protection in harsh environments such as high humidity, high temperature, and high salt fog, thereby solving the shortcoming of limited anti-corrosion effect of traditional rust inhibitors. The present invention introduces the molecular structure of carboxyl, ester and metal complex groups into the anti-rust formula. In the anti-rust process, the metal group can complex with the metal surface to form a stable complex film; while the carboxyl and ester groups enhance the anti-oxidation properties of the coating through chemical reactions, and give the coating a certain self-repairing ability. This chemical structure makes the activity of the rust inhibitor more durable, and is particularly suitable for anti-corrosion protection in harsh environments such as high humidity and high salt for a long time.
[0019] The water-based curing agent of the present invention uses a polymer resin with multiple cross-linking sites, and its molecular structure can be rapidly cross-linked during the curing process to form a network structure. This cross-linking structure makes the coating have better weather resistance and increases the stability of the coating in adverse environments.
[0020] The present invention improves the water resistance of the coating by modifying the resin molecular chain; introduces a hydrophobic modifier to enhance the water drop effect of the coating and avoid water penetration; controls the pH value and adjusts the acidic components to improve the stability of the emulsion and avoid the stability problem caused by phosphoric acid. DETAILED DESCRIPTION
[0021] The present invention is described in detail below by way of examples. The following examples are merely illustrative of the specific technical solutions of the present invention and do not limit the scope of the present invention. That is, it should be understood that non-essential simple corrections, adjustments and combinations made by those skilled in the art based on the inventive concept of the present invention are within the scope of the protection claimed in the present invention. In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained commercially.
[0022] The present invention provides raw materials and a preparation method of non-zinc-rich water-based primer.
[0023] The raw materials of the non-zinc-rich water-based primer include: a main agent and a curing agent, the main agent includes component A1 and component A2; the curing agent includes component B.
[0024] 1. In parts by weight, the formula of component A1 is as follows: Water: 5-25 parts; Dispersant: 1-3 parts; Filler: 30-40 parts; fillers include titanium dioxide, red iron oxide, yellow iron oxide, precipitated barium sulfate, talcum powder, wollastonite powder, and mica powder.
[0025] Rust inhibitor: 1-8 parts; the rust inhibitor includes aluminum tripolyphosphate.
[0026] Defoaming agent: 0.1-1 part; defoaming agent includes silicone-based defoaming agent.
[0027] Filler wetting agent: 0.1-1 part; filler wetting agent includes acrylate copolymer.
[0028] Water-based organic bentonite: 0.5-2 parts.
[0029] 2. In parts by weight, the formula of component A2 is as follows: Water-based epoxy emulsion: 30-40 parts; Defoaming agent: 0.1-1 part; the defoaming agent includes a biopolysaccharide-based defoaming agent.
[0030] Substrate wetting agent: 0.5-1 part; substrate wetting agents include polyoxyethylene ether.
[0031] Aqueous thickener: 0.2-1 part; aqueous thickeners include cellulose thickeners.
[0032] Co-solvent: 2-4 parts; Co-solvents include propylene glycol monobutyl ether (PNB) and dipropylene glycol monobutyl ether (DPNB).
[0033] Anti-flash rust agent: 0.5-2 parts; anti-flash rust agent includes sodium nitrite and homemade anti-flash rust agent.
[0034] 3. By weight, the formula of component B (curing agent) is as follows: Water-based curing agent: 10-40 parts; Water: 90-60 parts; Conditioner: 1-3 parts, conditioner includes homemade conditioner.
[0035] 4. Preparation method: Ingredients: Add the components of the main agent component A1 into a container according to proportion, stir evenly, and obtain formula A1.
[0036] Grinding: The main agent component A2 is fed into a grinding device for grinding, the particle size is controlled to be below 10 microns, and mixed to obtain formula A2.
[0037] Blending: Mix formula A2 with formula A1, perform physical stirring, and adjust the formula according to quality control parameters to obtain a coating.
[0038] Packaging: The paint is filtered to remove impurities and finally packaged.
[0039] It should be noted that the paint and curing agent are packaged separately. The two-component paint is composed of paint and curing agent. When used, the raw materials of the curing agent are mixed to obtain the curing agent, and then the paint and curing agent are mixed on site. The paint / curing agent mass ratio = 12 / 1 to obtain a non-zinc-rich water-based primer.
[0040] A more specific preparation method is given below: Example 1 In the formula of component A1, the preparation method of the silicone-based defoamer in the defoamer is as follows: At 50°C, 5 g of amino-terminated polydimethylsiloxane was reacted with 3 g of epoxidized vegetable oil (epoxidized linseed oil) in an anhydrous environment for 3 hours to form a copolymer.
[0041] 2 g of polyethylene glycol methacrylate, copolymer, and 1 g of dopamine hydrochloride were added to 90 ml of deionized water, and self-polymerization reaction was carried out under alkaline conditions (pH 8.5-9.0). After the reaction, 0.2 g of AIBN (azobisisobutyronitrile) was added, and the temperature was raised to 70°C for free radical polymerization. After the reaction, the mixture was cooled and stirred to room temperature to obtain a silicone-based defoaming agent.
[0042] in, Amodimethicone: Amodimethicone, Hubei Xinhongli Chemical Co., Ltd., 99%.
[0043] Polyethylene glycol methacrylate: Sigma-Aldrich, average Mn 360; Dopamine hydrochloride: Sigma-Aldrich, dopamine hydrochloride; Unless otherwise specified or specified by manufacturer or model, the purity of raw materials or reagents is 99%.
[0044] Example 2 In the formula of component A2, in the defoamer, the preparation method of the biopolysaccharide-based defoamer is as follows: 3g of bioactive polysaccharide is dissolved in 91ml of deionized water, heated to 60°C, and continuously stirred at 300rpm until completely dissolved. 5ml of vegetable oil and 1g of emulsifier are added, and emulsified at 1000rpm high-speed stirring for 15 minutes to obtain the biopolysaccharide-based defoamer.
[0045] in, Bioactive polysaccharides: xanthan gum, Sigma-Aldrich; Vegetable oil: soybean oil, Sigma-Aldrich; Emulsifier: lecithin, Sigma-Aldrich; Unless otherwise specified or specified by manufacturer or model, the purity of raw materials or reagents is 98%.
[0046] Example 3 In the formula of component A2, in the flash rust preventer, the preparation method of the homemade flash rust preventer is as follows: add 5g phytic acid and 70ml deionized water in a stirring container, stir evenly, keep the stirring speed at 300rpm, heat to 60°C until completely dissolved, and obtain a phytic acid solution. Add 2g of polyquaternary ammonium salt to the phytic acid solution, continue stirring for 30 minutes, then add 3g of silica aerogel, continue stirring for 60 minutes to obtain a mixed solution. Add 1g of indium methanesulfonate to the mixed solution, stir until completely dissolved, add 0.5g of trifluoroacetic acid, continue stirring at 70°C for 30 minutes, after the reaction is completed, add 2g of glycerol, continue stirring for 15 minutes, add the remaining deionized water, adjust to a total volume of 100ml, and obtain a homemade flash rust preventer.
[0047] in, Phytic acid: Sigma-Aldrich; Polyquaternium: Polyquaternium-7, Sigma-Aldrich; Silica aerogel: Sigma-Aldrich; Indium methanesulfonate: Sigma-Aldrich; Trifluoroacetic acid: Sigma-Aldrich; Glycerol: Sigma-Aldrich; Unless otherwise specified or specified by manufacturer or model, the purity of raw materials or reagents is 99%.
[0048] It should be noted that the complexation of phytic acid with metal ions can form a stable metal-phytic acid complex on the coating surface. These complexes effectively prevent the oxidation process by isolating the metal surface from contact with oxygen and water. This effect complements the surface activity of polyquaternary ammonium salts and jointly improves the anti-permeability and corrosion resistance of the coating. The combination of polyquaternary ammonium salts and silica aerogels shows a synergistic effect of the composite structure in water-based coatings. As a highly porous porous material, silica aerogel has ultra-low density and excellent thermal insulation, and polyquaternary ammonium salts, as a surfactant, can interact with the aerogel surface to form a uniform modified layer. The indium ions in indium methanesulfonate can interact with the silicon-oxygen bonds in the silica aerogel to form new metal-silicon complexes or metal oxide composites, which enhance the mechanical strength and corrosion resistance of the coating.
[0049] Example 4 In the formula of component B (curing agent), the preparation method of the water-based curing agent is as follows: Add 15g of polyamide resin and 5g of polyether polyol into a reaction container, raise the temperature to 80°C, maintain the temperature for 2 hours to obtain a prepolymer, then cool to 60°C, slowly add 3g of diisocyanate, react for 2 hours, then slowly add 1g of triethoxysilane at 60°C while maintaining stirring, cool to 40°C, add 2g of trimethylolpropane trimethacrylate to obtain a mixed solution.
[0050] 0.5 g of an emulsifier (triethanolamine) was dissolved in deionized water and then gradually added to the mixed solution, and cooled to room temperature at a stirring speed of 500 rpm to obtain a water-based curing agent.
[0051] It should be noted that by introducing the polyether block, a flexible chemical segment is formed in the polyamide resin, which significantly enhances the flexibility and ductility of the curing agent. Different from the traditional single amine cross-linking, the diisocyanate structure reacts with the amine group to form a hydrolysis-resistant urea structure, which gives the curing agent better hydrolysis resistance and chemical corrosion resistance. The Si-O-Si network structure formed by the condensation of triethoxysilane generates a highly cross-linked organic-inorganic composite structure in the curing agent, which can help improve the antioxidant and weather resistance of the cured film formed by the coating.
[0052] in, Polyamide resin: Haisu, HD02, amino-terminated hyperbranched polyamide, 99%.
[0053] Polyether polyol: Wanhua, polyether polyol, Mn ~500, 99%.
[0054] Diisocyanate: Tokyo Chemical Industry Co., Ltd. (TCI), diisocyanate, 99%.
[0055] Triethoxysilane: Sigma-Aldrich.
[0056] Trimethylolpropane trimethacrylate: Sigma-Aldrich.
[0057] Triethanolamine: Sigma-Aldrich.
[0058] Unless otherwise specified or specified by manufacturer or model, the purity of raw materials or reagents is 99%.
[0059] Example 5 In the formula of component B (curing agent), the preparation method of the homemade regulator is as follows: 1. Preparation of polymerized dopamine-modified graphene: 5 g of graphene oxide was dispersed in 400 ml of deionized water, treated under ultrasonic conditions for 30 minutes to obtain a dispersion, and then 3 g of dopamine hydrochloride was added to the dispersion, and the stirring condition was maintained and reacted at room temperature for 24 hours, and then 1 g of titanium dioxide nanoparticles was added, and stirring was continued for 6 hours, and then 1 g of perfluorooctyltriethoxysilane was continued, and then 50 ml of ethanol was added, and stirring was continued for 12 hours. The reaction mixture was centrifuged and washed alternately with deionized water and ethanol for 3 times to remove unreacted residues, and the washed composite material was dried in a vacuum drying oven to obtain polymerized dopamine-modified graphene.
[0060] 2. Preparation of silicone polyether block copolymer: Add 10g of terminal hydroxyl polydimethylsiloxane and 50ml of dimethylformamide (DMF) into a container, stir evenly, add 3g of epoxy silane, keep the stirring speed at 300rpm, control the temperature at 70°C, react for 2 hours, then add 5g of polyethylene glycol, continue stirring and control the temperature at 80°C, add 0.1g of dibutyltin dilaurate, the reaction time is 3 hours, then add 2g of silicone compound to the reaction solution, continue stirring, and keep the temperature at 70°C. After the reaction is completed, remove the DMF solvent from the mixture by a rotary evaporator to obtain a concentrated block copolymer, wash the copolymer with ethanol to remove unreacted residues, then separate the product by centrifugation, and then dry it in a vacuum drying oven to obtain a silicone polyether block copolymer.
[0061] 3. Preparation of the regulator: Add 10g of polyetheramine and 60ml of deionized water to a container, keep the stirring speed at 300rpm, heat to 50°C to fully dissolve the polyetheramine, then add 1g of polymerized dopamine-modified graphene, continue stirring for 1 hour, keep the temperature at 50°C, add 3g of silicone polyether block copolymer, continue stirring at 60°C for 45 minutes, add 2g of triethanolamine, and stir for 30 minutes, add 0.5g of AIBN and 2g of ethylene glycol monoethyl ether to the mixture, continue stirring and heat to 70°C, the reaction time is 2 hours, after the reaction is completed, cool to room temperature, add the remaining deionized water, adjust the total volume to 100ml, and obtain a homemade regulator.
[0062] in, Graphene oxide: Sigma-Aldrich; Dopamine hydrochloride: Sigma-Aldrich, dopamine hydrochloride; Titanium dioxide nanoparticles: Sigma-Aldrich, 150 nm; Hydroxy-terminated polydimethylsiloxane: Gelest Inc.; purity 99%.
[0063] Polyethylene glycol: Sigma-Aldrich, PEG-2000, purity 99%.
[0064] Epoxy silane: Evonik Industries, Dynasylan® GLYMO, purity: ≥98% Organosilicon compound: Momentive Performance Materials, Silquest A-1230.
[0065] Polyetheramine: Polyetheramine D230, Jeffamine® D-230, Huntsman.
[0066] Unless otherwise specified or specified by manufacturer or model, the purity of raw materials or reagents is 99%.
[0067] It should be noted that the polymerized dopamine-modified graphene combines the adhesion properties of dopamine and the high strength properties of graphene, which can significantly improve the interfacial stability of the regulator and enhance the durability of the coating. The silicone polyether block copolymer forms a bridge structure between the aqueous and organic phases, making the regulator have super compatibility and shear resistance, which is particularly suitable for application in epoxy coatings. Through the combination of polyetheramine and polymerized dopamine-modified graphene, coupled with the complexation of triethanolamine, the regulator has better modification function and can better stabilize the coating in complex environments.
[0068] The following comparative experiment is set up: Example 6 By weight, the formula of non-zinc-rich water-based primer is: Component A1: Water: 20 parts; Dispersant: 2 parts; Filler (titanium dioxide): 35 parts; Rust inhibitor (aluminum tripolyphosphate): 5 parts; Defoamer (self-made silicone-based defoamer of Example 1): 0.5 parts; Filler wetting agent (acrylate copolymer): 0.5 parts; Water-based organic bentonite: 1 part; Component A2: Water-based epoxy emulsion: 35 parts; Defoamer (self-made biopolysaccharide-based defoamer of Example 2): 0.5 parts; Substrate wetting agent (polyoxyethylene ether): 0.5 parts; Water-based thickener (cellulose thickener): 0.5 parts; Cosolvent (PNB): 3 parts; Anti-flash rust agent (self-made anti-flash rust agent of Example 3): 1.5 parts; Component B: Water-based curing agent (self-made water-based curing agent in Example 4): 30 parts; Water: 70 parts; Regulator (self-made regulator of Example 6): 2 parts.
[0069] in, Dispersant: Disperbyk® 190, BASF; Titanium dioxide: Ti-Pure™ R-706, Chemours; Acrylate copolymer: Efka® FL 3772, BASF; Water-based organobentonite: Bentone® SD-1, Elementis; Water-based epoxy emulsion: EPICLON H-502-42W, DIC; Polyoxyethylene ether: Sigma-Aldrich; Cellulosic thickener: CELLOSIZE™ hydroxyethylcellulose (HEC), Dow Inc.
[0070] Unless otherwise specified or specified by manufacturer or model, the purity of raw materials or reagents is 99%.
[0071] Example 7 In this embodiment, the amount of the regulator added is increased, which is different from that in embodiment 6. Regulator (self-made regulator of Example 6): 3 parts.
[0072] The rest is the same as Example 6.
[0073] Example 8 In this embodiment, the amount of the anti-flash rust agent added is increased, which is different from that in embodiment 6. Anti-flash rust agent (self-made anti-flash rust agent of Example 3): 2 parts.
[0074] The rest is the same as Example 6.
[0075] Example 9 In this embodiment, the amount of defoamer added is reduced, which is different from that in embodiment 6. In component A1, Defoamer (self-made silicone-based defoamer of Example 1): 0.1 part; In component A2, Defoamer (self-made biopolysaccharide-based defoamer of Example 2): 0.1 part; The rest is the same as Example 6.
[0076] Example 10 In this embodiment, the amount of water-based curing agent added is increased, which is different from that in embodiment 6. Water-based curing agent (self-made water-based curing agent in Example 4): 40 parts; The rest is the same as Example 6.
[0077] Comparative Example 1 Different from Example 6, In component B, Conditioner (commercially available product, Dow, AMP-95): 2 parts.
[0078] The rest is the same as Example 6.
[0079] Comparative Example 2 Different from Example 6, In component A2, Anti-flash rust agent (commercially available product, Halox Flash-X 150): 1.5 parts.
[0080] The rest is the same as Example 6.
[0081] Comparative Example 3 Different from Example 6, In component A1, Defoaming agent (commercially available product, BYK-022): 0.5 parts; In component A2, Defoaming agent (commercially available product, BYK-022): 0.5 parts; The rest is the same as Example 6.
[0082] Comparative Example 4 Different from Example 6, In component B, Water-based curing agent (commercial product, Araldite® PY 306, Huntsman): 2 parts; The rest is the same as Example 6.
[0083] The formulations of Examples 6 to 10 and Comparative Examples 1 to 4 were prepared into primers using the aforementioned preparation method and then tested. The testing process also reflected the application of the primer of the present invention in composite materials. The composite material includes a substrate, the material of the substrate can be steel, and the primer is coated on the substrate.
[0084] Detection method: 1. Prepare a steel plate sample of 1.6mm×76mm×152mm (thickness×width×length), which is suitable for Taber wear tester. The steel plate used can be selected to comply with Japanese Industrial Standard JIS G3101. The sandblasting of the steel plate needs to meet Swedish standard Sa2.5 level, and the surface roughness reaches BM9 in Rugotest No.3 (average roughness 25-40μ, maximum roughness 90μ). Apply the primer on the steel plate sample, first measure the dry film thickness (DFT), and the dry film thickness is controlled at 20-40μm.
[0085] 2. Then, the steel plate is exposed to a hot and humid / corrosive environment for 56 days according to the IICL test box standard, specifically: Conduct moisture and heat resistance / corrosion cycle test: First, perform a wet heat cycle: 8 hours of 60°C UV exposure, 4 hours of 50°C condensed water exposure, and repeat for 72 hours.
[0086] The corrosion cycle was then repeated for 96 hours: 4 hours of exposure to wet salt spray at 30°C, and 2 hours of exposure to dry conditions at 40°C.
[0087] The humidity and heat cycle and corrosion cycle were repeated for 8 cycles, with a total duration of 56 days.
[0088] 3. After the steel plate has been exposed for 56 days, the final performance evaluation is carried out, and the evaluation time is preferably controlled within 1 hour: Anti-corrosion properties: The blister test refers to ASTM D714; The rust level test refers to ASTM D610.
[0089] 4. Calculate the score after testing The bubble size and density are determined according to ASTM D714. The bubble size is divided into numerical grades from 10 to 0 according to the size. Grade 10 represents no blistering, and the 11 grades correspond to 20-0 points in a descending or deteriorating manner. Each grade differs by 2 points. Grade 10 corresponds to 20 points and grade 0 corresponds to 0 points.
[0090] The bubble density is divided into five levels: none, very few, medium, medium dense, and dense, corresponding to 20-0 points respectively. Specifically, none corresponds to 20 points, very few corresponds to 15 points, medium corresponds to 10 points, medium dense corresponds to 5 points, and dense corresponds to 0 point.
[0091] Compare with the scale and legend of ASTM D610 to confirm the rust grade (10-1, deteriorating in sequence), 10 grades correspond to 10-1 points, each grade differs by 1 point, 10 grades correspond to 10 points, and 1 grade corresponds to 0 points.
[0092] Perform 10 parallel experiments, calculate the average score, and also calculate the sum of the average scores of (bubble size + bubble density + corrosion condition). Taking Example 6 as an example, 18.8 + 19.0 + 9.5 = 47.3. The results are shown in Table 1.
[0093] Table 1
[0094] Analysis: In Example 7, the amount of the regulator was increased, in Example 8, the amount of the flash rust preventer was increased, in Example 9, the amount of the defoamer was reduced, and in Example 10, the amount of the curing agent was increased. Comparative Examples 1 to 4 were compared using commercially available products. It can be seen from the experimental data that the primer of the present invention performs better in terms of weather resistance, stability and rust resistance.
[0095] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. Non-zinc-rich water-based primer, characterized in that: It includes a main agent and a curing agent, the main agent includes component A1 and component A2; the curing agent includes component B; component A1 includes the following raw materials: water, dispersant, filler, rust inhibitor, defoamer, filler wetting agent, water-based organic bentonite; component A2 includes the following raw materials: water-based epoxy emulsion, defoamer, substrate wetting agent, water-based thickener, cosolvent, anti-flash rust agent; component B includes the following raw materials: water-based curing agent, water, regulator.
2. The non-zinc-rich water-based primer according to claim 1, characterized in that: The filler includes at least one of titanium dioxide, red iron oxide, yellow iron oxide, precipitated barium sulfate, talcum powder, wollastonite powder and mica powder; and the rust inhibitor includes aluminum tripolyphosphate.
3. The non-zinc-rich water-based primer according to claim 1, characterized in that: The defoaming agent includes at least one of an organosilicon-based defoaming agent and a biopolysaccharide-based defoaming agent; the filler wetting agent includes an acrylate copolymer; the substrate wetting agent includes polyoxyethylene ether; the aqueous thickener includes a cellulose thickener; the cosolvent includes at least one of propylene glycol monobutyl ether and dipropylene glycol monobutyl ether; the anti-flash rust agent includes at least one of sodium nitrite and a homemade anti-flash rust agent; and the regulator includes at least one of a homemade regulator and 2-amino-2-methyl-1-propanol.
4. The non-zinc-rich water-based primer according to claim 3, characterized in that: The preparation method of an organosilicon-based defoamer comprises the following steps: amino-terminated polydimethylsiloxane reacts with epoxidized vegetable oil to generate a copolymer; polyethylene glycol methacrylate, the copolymer and dopamine hydrochloride are added into water and reacted under alkaline conditions; after the reaction is completed, an initiator is added and the temperature is increased for polymerization; after the reaction, the mixture is cooled and stirred to room temperature to obtain an organosilicon-based defoamer.
5. The non-zinc-rich water-based primer according to claim 3, characterized in that: The preparation method of the biopolysaccharide-based defoamer comprises the following steps: dissolving the bioactive polysaccharide, adding vegetable oil and an emulsifier, and emulsifying under stirring to obtain the biopolysaccharide-based defoamer.
6. The non-zinc-rich water-based primer according to claim 3, characterized in that: The preparation method of a self-made anti-flash rust agent comprises the following steps: preparing phytic acid into a phytic acid solution, adding polyquaternary ammonium salt and silica aerogel into the phytic acid solution to obtain a mixed solution; adding indium methanesulfonate and trifluoroacetic acid into the mixed solution, and after the reaction is completed, adding glycerol and water to obtain the self-made anti-flash rust agent.
7. The non-zinc-rich water-based primer according to claim 3, characterized in that: The preparation method of a homemade regulator comprises the following steps: preparing polymerized dopamine-modified graphene: preparing a dispersion of graphene oxide, then adding dopamine hydrochloride to the dispersion, reacting, then adding titanium dioxide nanoparticles, perfluorooctyltriethoxysilane and ethanol, centrifuging the reaction mixture after the reaction, washing and drying to obtain polymerized dopamine-modified graphene; adding terminal hydroxyl polydimethylsiloxane and dimethylformamide in a container, stirring evenly, adding epoxy silane, reacting, then adding polyethylene glycol and dibutyltin dilaurate, adding an organosilicon compound to the reaction solution after the reaction, concentrating after the reaction, washing and drying to obtain an organosilicon polyether block copolymer; adding polymerized dopamine-modified graphene, an organosilicon polyether block copolymer, triethanolamine, an initiator and ethylene glycol monoethyl ether after the polyetheramine is dissolved, cooling to room temperature after the reaction, adjusting the total volume to obtain a homemade regulator.
8. The non-zinc-rich water-based primer according to claim 1, characterized in that: The preparation method of the water-based curing agent comprises the following steps: reacting a polyamide resin and a polyether polyol to obtain a prepolymer, then cooling and adding diisocyanate, adding triethoxysilane after the reaction, cooling and adding trimethylolpropane trimethacrylate after the reaction to obtain a mixed solution, dissolving an emulsifier and adding the mixed solution, stirring and cooling, and obtaining the water-based curing agent.
9. The method for preparing a non-zinc-rich water-based primer according to any one of claims 1 to 8, characterized in that: The steps include: Ingredients: Mix the raw materials of component A1 evenly to obtain formula A1; Grinding: Grind the raw materials of component A2 and mix well to obtain formula A2; Blending: Mix formula A2 and formula A1 to obtain a coating; Mixing: Mix the raw materials of component B to obtain formula B, and mix the coating and formula B to obtain a non-zinc-rich water-based primer.
10. A composite material, characterized in that It comprises a substrate, on which a non-zinc-rich water-based primer is formed into a dry film, and the thickness of the dry film is controlled at 20-40 μm, wherein the non-zinc-rich water-based primer is prepared according to the preparation method of the non-zinc-rich water-based primer according to claim 9.
Citation Information
Patent Citations
High-efficient water reducing agent
CN107814506A
Emulsion type fluorine-containing organosilicone defoaming agent for oil and aqueous two-phase system and preparation method thereof
CN108159738A
High-viscosity water-based asphalt waterproof coating and preparation method thereof
CN113667404A
Preparation method of polyurethane modified nonionic aqueous amine epoxy resin curing agent
CN113956442A
Waterborne epoxy primer as well as preparation method and application thereof
CN116004084A
Cited By
Water-based paint anti-flash-rust agent and preparation method and application thereof
CN119552531A